2017
DOI: 10.1002/2017ja023906
|View full text |Cite
|
Sign up to set email alerts
|

A multispacecraft study of a small flux rope entrained by rolling back magnetic field lines

Abstract: We present a small flux rope (SFR) with smooth magnetic field rotations entrained by rolling back magnetic field lines around 1 AU. Such SFRs have only been seldom reported in the literature. This SFR was adjacent to a heliospheric plasma sheet (HPS), which is defined as a high plasma beta region in the vicinity of a heliospheric current sheet. Even though the SFR and HPS have different plasma beta, they possess similar plasma signatures (such as temperature, density, and bulk speed), density ratio of alpha pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…As suggested in the introduction, most small transients occur in slow solar wind, and they have some characteristics (e.g., enhanced magnetic field strength, low plasma beta, Alfvén Mach number) based on statistical studies (Yu et al 2014(Yu et al , 2016. Furthermore, the above statistical results clearly show that the signatures of small transients vary greatly (as shown by the large error bars in (Janvier et al 2014;Huang et al 2017).…”
Section: Small Solar Transientmentioning
confidence: 61%
See 2 more Smart Citations
“…As suggested in the introduction, most small transients occur in slow solar wind, and they have some characteristics (e.g., enhanced magnetic field strength, low plasma beta, Alfvén Mach number) based on statistical studies (Yu et al 2014(Yu et al , 2016. Furthermore, the above statistical results clearly show that the signatures of small transients vary greatly (as shown by the large error bars in (Janvier et al 2014;Huang et al 2017).…”
Section: Small Solar Transientmentioning
confidence: 61%
“…The HCS is defined as a sustained change in signs of the magnetic field; it is accepted as a separation for the different polarity of the interplanetary magnetic field (Crooker et al 2004;Liu et al 2014) when it is consistent with TSB, which is defined as the change in direction of PADs (Kahler et al 1996;Foullon et al 2009). When the magnetic field lines roll back, HCS is separated from TSB (Owens et al 2013;Huang et al 2017). Thus, the low density region solar wind does not depend on the streamer belt structure or on HCS.…”
Section: Event Twomentioning
confidence: 99%
See 1 more Smart Citation
“…Rouillard et al (, ) confirmed this result by tracing several SFRs back to their source regions. But whether they are released through interchange reconnection processes (Huang et al, ; Wang et al, ) or pinched off by the intrinsic instability‐driven magnetic reconnection processes (Chen et al, ) still needs further investigation. The other category may be related to X‐ray jets that arise from the photosphere (Janvier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…By utilizing STEREO A data, Yu et al () investigated the Q <Fe> variations in small transients, an extended range of SFRs, and they demonstrated that Q <Fe> only increases in less than 5% of small transients. Moreover, Huang et al () traced a SFR, which is entrained by rolling back magnetic field lines, back to its source region in the cusp of the streamer belt with the support of N α / N p and heavy ion compositions. SFRs are more influenced than MCs by ambient solar wind due to their small sizes (Feng & Wang, ; Janvier et al, ), but the Q <Fe> variations, which are frozen‐in within several solar radii, can be used to exclude propagation effects and provide evolutionary properties on the conditions at the origin (Huang et al, ; Lepri et al, ; von Steiger et al, ).…”
Section: Introductionmentioning
confidence: 99%